1996
DOI: 10.7164/antibiotics.49.553
|View full text |Cite
|
Sign up to set email alerts
|

Ascosteroside, a New Antifungal Agent from Ascotricha amphitricha. II. Isolation and Structure Elucidation.

Abstract: The novel antifungal agent ascosteroside (1) was isolated from cultured broth of Ascotricha amphitricha (ATCC74237). The structure based on spectroscopic data was determined to be an a-linked glycoside of a lanostane-type triterpenoid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 7 publications
0
14
0
Order By: Relevance
“…Mycelial crude extract (2.2 g) was processed by chromatography on silica gel; elution with cyclohexane/EtOAc (40:60) yielded 416 mg intermediate product which was separated by HPLC as above, affording 24 mg compound 5 and 62 mg compound 6. Compound 5 was found to identical to ascosteroside previously isolated from the ascomycete Ascotricha amphitricha (Leet et al, 1996) 3436,2922,2874,1693,1652,1458,1381,1202,1148,1069,1033,977,908,785,726,685 and 622 cm À1 . UV (MeOH) k max (e) 202 (13257), 230 (sh, 4498), 280 (77) nm.…”
Section: Isolation Of Ascosteroside B (6)mentioning
confidence: 93%
See 1 more Smart Citation
“…Mycelial crude extract (2.2 g) was processed by chromatography on silica gel; elution with cyclohexane/EtOAc (40:60) yielded 416 mg intermediate product which was separated by HPLC as above, affording 24 mg compound 5 and 62 mg compound 6. Compound 5 was found to identical to ascosteroside previously isolated from the ascomycete Ascotricha amphitricha (Leet et al, 1996) 3436,2922,2874,1693,1652,1458,1381,1202,1148,1069,1033,977,908,785,726,685 and 622 cm À1 . UV (MeOH) k max (e) 202 (13257), 230 (sh, 4498), 280 (77) nm.…”
Section: Isolation Of Ascosteroside B (6)mentioning
confidence: 93%
“…After dereplication studies with common databases (DNP), 1 H and 13 C NMR data (Table 2) revealed the similarity of compound 6 with ascosteroside A (5, Leet et al, 1996). The 13 C NMR spectrum of 6 showed 36 signals.…”
Section: Ascosterosides a (5) And B (6)mentioning
confidence: 98%
“…Exponential-phase C. albicans MY1055 cells in CMS at 10 6 CFU/ml were treated for 30 min at 30°C with increasing concentrations of inhibitors. The treated cells were pulse-labeled for an additional 30 14 C-labeled amino acid per ml. Radiolabeling was quenched by the addition of an equal volume of 10% trichloroacetic acid (TCA).…”
Section: Methodsmentioning
confidence: 99%
“…1, which inhibit ␤-(1,3)-Dglucan synthase. Two of the compounds, ascosteroside (18,30), also known as L-767812 (8; J. R. Thompson, S. Dreikorn, J. Onishi, M. Meinz, C. Jue, J. Curotto, and M. Kurtz, Conf. Yeast Genet.…”
mentioning
confidence: 99%
“…[4][5][6]9) On the basis of the above evidence as well as the precise spectral comparisons of 1 and analogous nortriterpenes, 10-12) the structure of 1 was concluded to be 24-ethyl,24-methyl-29-nor-5a-lanosta-4(28),7,25-trien-3b-ol. On the basis of the above evidence as well as the precise spectroscopic comparisons of 2 and analogous nortriterpenes, [10][11][12] the structure of 2 was concluded to be 24-ethyl,24-methyl-29-nor-5a-lanosta-4(28),7-dien-3b-ol.…”
mentioning
confidence: 99%